(untitled) (Polish Yearbook of International Law, 2024)
The divergence between Russia and Western States on the question whether international humanitarian law (IHL) applies to cyber space is still omnipresent in the debates at the UN Open-ended Working Group. Russia has several times submitted a draft or a concept for a binding legal instrument; however, they have not included considerable suggestions on IHL. Furthermore, Russia is actively using cyber means in an aggressive war against Ukraine, which makes its calls sound hollow. How then can one explain Russia’s quest for a treaty for cyberspace, especially regarding IHL? This article aims to shed some light on this question in the broader context of Russian approaches to international law-making and its historic role in developing IHL rules.